Whole-exome identifies germline variants in families with obstructive sleep apnea syndrome - de Azevedo, Pedro Guimarães; Guimarães, Maria de Lourdes Rabelo; Albuquerque, Anna Luiza Braga; Alves, Rayane Benfica; Gomes Fernandes, Bianca; Marques de Melo, Flavia; Guimaraes Corrêa Do Carmo Lisboa Cardenas, Raony; Friedman, Eitan; De Marco, Luiz; Bastos-Rodrigues, Luciana (Frontiers in Genetics, 2023)
Background: Obstructive sleep apnea syndrome (OSAS) (OMIM #107650) is characterized by complete or partial obstruction of the upper airways, resulting in periods of sleep associated apnea. OSAS increases morbidity and mortality risk from cardiovascular and cerebrovascular diseases. While heritability of OSAS is estimated at ~40%, the precise underlying genes remain elusive. Brazilian families with OSAS that follows as seemingly autosomal dominant inheritance pattern were recruited. Methods: The study included nine individuals from two Brazilian families displaying a seemingly autosomal dominant inheritance pattern of OSAS. Whole exome sequencing of germline DNA were analyzed using Mendel,MD software. Variants selected were analyzed using Varstation® with subsequent analyses that included validation by Sanger sequencing, pathogenic score assessment by ACMG criteria, co-segregation analyses (when possible) allele frequency, tissue expression patterns, pathway analyses, effect on protein folding modeling using Swiss-Model and RaptorX. Results: Two families (six affected patients and three unaffected controls) were analyzed. A comprehensive multistep analysis yielded variants in COX20 (rs946982087) (family A), PTPDC1 (rs61743388) and TMOD4 (rs141507115) (family B) that seemed to be strong candidate genes for being OSAS associated genes in these families. Conclusions: Sequence variants in COX20, PTPDC1 and TMOD4 seemingly are associated with OSAS phenotype in these families. Further studies in more, ethnically diverse families and non-familial OSAS cases are needed to better define the role of these variants as contributors to OSAS phenotype.